Springboard oscillation during hurdle flight - Miller, D. I.; Osborne, M. J.; Jones, I. C. (Journal of Sports Sciences, 1998)
The relative influences of board-tip rebound and fulcrum setting upon vertical board-tip oscillation during hurdle flight were investigated to gain insight into the mechanism by which highly skilled divers are able to make effective contact with the springboard. Data were collected on running dives executed by 3-m finalists at the 1995 World Diving Cup (men), the 1996 Olympic Games (women) and the 1996 US Junior Olympics (boys and girls). Analysis of the vertical board-tip patterns of motion during hurdle flight revealed substantial deviations from a regular damped oscillation, particularly during the first excursion above the horizontal. The latter was characterized by two peaks, the first resulting from upward momentum and the second due to the board's colliding with the fulcrum. A regression analysis of the senior divers' data indicated that 83.7% of the variance in hurdle flight time could be accounted for by the maximum height reached by the board-tip and only 3.6% by fulcrum setting. We conclude that, among senior divers, rebound of the springboard was the dominant factor influencing the length of time required for the board to complete its characteristic 2.25 and 2.50 cycles before take-off.